Transcoding the world: Haraway's postmodernism. - Crewe, Jonathan (Signs: Journal of Women in Culture & Society)
Opinion. Gives a detailed overview on the transcoding found in the postmedullary works of Donna Haraway. Background information on Haraway; Detailed information on Harraway's work; Implications of Haraway's cyborg transcoding table; How the postmodern world is presented to Haraway.